Ordering Urban Space and Migrants’ Protests in Sabongari, Kano, 1911 - 1960 (2011)
Urban segregation policy represents one of the dramatic changes fostered by colonialism with far reaching impact on politics of protests and identity consciousness among immigrants. It is argued that despite the considerable body of interdisciplinary studies that the theme of urban segregation generated, urban historiography in Nigeria has been influenced by the paradigms of Universalist ethic ofpublic health and political development to the exclusion of power structures. The paper theorises on politics of protests, search for identity and resistance of the subalterns and migrants in Sabongari Kano against colonial policies to control over-urbanisation processes between 1911 and 1960. Plot Holders’ Association, Sabongari resisted attempts by the colonial officials to demolish over-built and over- populated plots without due regards to livelihoods, taxation, family values, and indeed, the Building Ordinance that came into existence almost two decades after such buildings were constructed. In British Africa, urban segregation policies such as Sabongari system were predicated on public health, religious and cultural differences but there were political and economic interests as well. The paper further explores how colonial segregation policy in Sabongari fostered over-urbanisation illustrated by overcrowding, poor sanitation, infectious diseases, unemployment, prostitution, overstressed social infrastructure and crime unequalled in the Kano urban complex.